Congruence of local ecological knowledge (LEK)‐based methods and line‐transect surveys in estimating wildlife abundance in tropical forests. Issue 3 (5th December 2021) - Braga‐Pereira, Franciany; Morcatty, Thais Q.; El Bizri, Hani R.; Tavares, Aline S.; Mere‐Roncal, Carla; González‐Crespo, Carlos; Bertsch, Carolina; Rodriguez, Claudia Ramos; Bardales‐Alvites, Claudio; von Mühlen, Eduardo M.; Bernárdez‐Rodríguez, Galicia Fernanda; Paim, Fernanda Pozzan; et al.
Abstract: Effective estimation of wildlife population abundance is an important component of population monitoring, and ultimately essential for the development of conservation actions. Diurnal line‐transect surveys are one of the most applied methods for abundance estimations. Local ecological knowledge (LEK) is empirically acquired through the observation of ecological processes by local people. LEK‐based methods have only been recognized as valid scientific methods for surveying fauna abundance in the last three decades. However, the agreement between both methods has not been extensively analysed. We compared concomitant abundance data for 91 wild species (mammals, birds and tortoises) from diurnal line transects (9, 221 km of trails) and a LEK‐based method (291 structured interviews) at 18 sites in Central and Western Amazonia. We used biological and socioecological factors to assess the agreements and divergences between abundance indices obtained from both methods. We found a significant agreement of population abundance indices for diurnal and game species. This relationship was also positive regardless of species sociality (solitary or social), body size and locomotion mode (terrestrial and arboreal); and of sampled forest type (upland and flooded forests). Conversely, we did not find significant abundance covariances for nocturnal and non‐game species. Despite the general agreement between methods, line transects were not effective at surveying many species occurring in the area, with 40.2% and 39.8% of all species being rarely and never detected in at least one of the survey sites. On the other hand, these species were widely reported by local informants to occur at intermediate to high abundances. Although LEK‐based methods have been long neglected by ecologists, our comparative study demonstrated their effectiveness for estimating vertebrate abundance of a wide diversity of taxa and forest environments. This can be used simultaneously with line‐transect surveys to calibrate abundance estimates and record species that are rarely sighted during surveys on foot, but that are often observed by local people during their daily extractive activities. Thus, the combination of local and scientific knowledge is a potential tool to improve our knowledge of tropical forest species and foster the development of effective strategies to meet biodiversity conservation goals. Resumen: La estimación eficaz de la abundancia de las poblaciones de fauna silvestre es un importante componente del monitoreo poblacional, y, en último término, es fundamental para el desarrollo de actividades dirigidas a la conservación. Los transectos lineales diurnos son uno de los métodos más frecuentemente utilizados para estimar la abundancia. El Conocimiento Ecológico Local (LEK) se adquiere de forma empírica a través de una aproximación más holística y ecocéntrica de los procesos ecológicos. Los métodos basados en LEK sólo han sido reconocidos como método científico de monitoreo de fauna silvestre en las últimas tres décadas. Sin embargo, aún no se ha evaluado en profundidad la concordancia entre ambos métodos. En este estudio comparamos la abundancia relativa de 91 especies silvestres (mamíferos, aves y tortugas) obtenida a partir de transectos lineales diurnos (9, 221 km de recorrido) y de un método basado en LEK (291 entrevistas estructuradas) en 18 sitios de la Amazonía Central y Oeste. Usamos factores socio‐ecológicos y biológicos para analizar las concordancias y divergencias entre la índices de abundancia estimada mediante ambos métodos. Se observó concordancia en los índices de abundancia poblacional de especies diurnas y especies cinegéticas estimada mediante ambos métodos. Esta concordancia fue independiente de la sociabilidad de la especie (solitaria o social), tamaño corporal, modo de locomoción (terrestre o arbórea), y tipo de bosque (bosque de altura e inundable). A la inversa, no se observó concordancia en el índice abundancia de especies nocturnas y no‐cinegéticas. A pesar de la concordancia general entre ambos métodos, los transectos lineales diurnos no fueron efectivos para monitorear muchas de las especies, con un 40.2% y 39.8% de todas las especies poco frecuentes (<0.1 individuos/km) o no detectadas, respectivamente, en al menos uno de los sitos muestreados. Algo que llama la atención, ya que la mayor parte de los informantes locales reportaron que las abundancias de esas especies eran intermedias o elevadas. Aunque los ecólogos han tendido a infravalorar los métodos basados en LEK, nuestro estudio comparativo muestra la eficacia de estos métodos para estimar el índice de abundancia de vertebrados en una amplia variedad de taxones y de ambientes. Los métodos basados en LEK son rentables y pueden ayudar a superar las restricciones financieras y logísticas propias del monitoreo de fauna continuado y de largo término de proyectos de conservación. Así, la combinación del conocimiento local y científico podría ser una herramienta importante para mejorar el conocimiento sobre especies tropicales y para promover el desarrollo de estrategias efectivas que permitan cumplir con los objetivos de conservación de la biodiversidad.